Framework for Effectiveness Human Resource Management in Compliance of Safety in Construction Industry - Abd Rahim, Nur Ezzati Alya (Universiti Teknologi PETRONAS, 2020)
Construction projects experience various problems and complex factors. Construction sector is diverse as it contains sub-contractors, contractors, consultants, architects, owners, and others. The aim of this paper is to identify and analyze the factor that affected the effectiveness of human resource towards safety compliance in construction project and identify significant methods or recommendations to improve them. Other than that, to ascertain the significance of the resource management as one of the key elements in construction project success. A literature review and a questionnaire survey will be done for data collection before being analyzed and ranked considering Relative Importance Index and Cronbach’s alpha. The questionnaires will be distributed to construction workers at any construction project area Perak and the feedbacks obtained will be used for the case study for further clarification. The results of the study will be collected and further discussed during the next academic semester for Final Year Project 2.